Micro-Level Analysis of Farmers’ Adaptation to Climate Change in Southern Africa - Nhemachena, Charles; Hassan, Rashid M. (RePEc: Research Papers in Economics, 2007)
Adaptation to climate change involves changes in agricultural management practices in response to changes in climate conditions. It often involves a combination of various individual responses at the farm-level and assumes that farmers have access to alternative practices and technologies available in the region. This study examines farmer adaptation strategies to climate change in Southern Africa based on a cross-section database of three countries (South Africa, Zambia and Zimbabwe) collected as part of the Global Environment Facility/World Bank (GEF/WB) Climate Change and African Agriculture Project. The study describes farmer perceptions to changes in long-term temperature and precipitation as well as various farm-level adaptation measures and barriers to adaptation at the farm household level. A multivariate discrete choice model is used to identify the determinants of farm-level adaptation strategies. Results confirm that access to credit and extension and awareness of climate change are some of the important determinants of farm-level adaptation. An important policy message from these results is that enhanced access to credit, information (climatic and agronomic) as well as to markets (input and output) can significantly increase farm-level adaptation. Government policies should support research and development on appropriate technologies to help farmers adapt to changes in climatic conditions. Examples of such policy measures include crop development, improving climate information forecasting, and promoting appropriate farm-level adaptation measures such as use of irrigation technologies. from Authors' Abstract
Keywords: openalex:import

Micro-Level Analysis of Farmers’ Adaptation to Climate Change in Southern Africa - Nhemachena, Charles; Hassan, Rashid M. (RePEc: Research Papers in Economics, 2007)
Adaptation to climate change involves changes in agricultural management practices in response to changes in climate conditions. It often involves a combination of various individual responses at the farm-level and assumes that farmers have access to alternative practices and technologies available in the region. This study examines farmer adaptation strategies to climate change in Southern Africa based on a cross-section database of three countries (South Africa, Zambia and Zimbabwe) collected as part of the Global Environment Facility/World Bank (GEF/WB) Climate Change and African Agriculture Project. The study describes farmer perceptions to changes in long-term temperature and precipitation as well as various farm-level adaptation measures and barriers to adaptation at the farm household level. A multivariate discrete choice model is used to identify the determinants of farm-level adaptation strategies. Results confirm that access to credit and extension and awareness of climate change are some of the important determinants of farm-level adaptation. An important policy message from these results is that enhanced access to credit, information (climatic and agronomic) as well as to markets (input and output) can significantly increase farm-level adaptation. Government policies should support research and development on appropriate technologies to help farmers adapt to changes in climatic conditions. Examples of such policy measures include crop development, improving climate information forecasting, and promoting appropriate farm-level adaptation measures such as use of irrigation technologies. from Authors' Abstract
Keywords: openalex:import

Micro-Level Analysis of Farmers’ Adaptation to Climate Change in Southern Africa - Nhemachena, Charles; Hassan, Rashid M. (RePEc: Research Papers in Economics, 2007)
Adaptation to climate change involves changes in agricultural management practices in response to changes in climate conditions. It often involves a combination of various individual responses at the farm-level and assumes that farmers have access to alternative practices and technologies available in the region. This study examines farmer adaptation strategies to climate change in Southern Africa based on a cross-section database of three countries (South Africa, Zambia and Zimbabwe) collected as part of the Global Environment Facility/World Bank (GEF/WB) Climate Change and African Agriculture Project. The study describes farmer perceptions to changes in long-term temperature and precipitation as well as various farm-level adaptation measures and barriers to adaptation at the farm household level. A multivariate discrete choice model is used to identify the determinants of farm-level adaptation strategies. Results confirm that access to credit and extension and awareness of climate change are some of the important determinants of farm-level adaptation. An important policy message from these results is that enhanced access to credit, information (climatic and agronomic) as well as to markets (input and output) can significantly increase farm-level adaptation. Government policies should support research and development on appropriate technologies to help farmers adapt to changes in climatic conditions. Examples of such policy measures include crop development, improving climate information forecasting, and promoting appropriate farm-level adaptation measures such as use of irrigation technologies. from Authors' Abstract
Keywords: openalex:import

Micro-Level Analysis of Farmers’ Adaptation to Climate Change in Southern Africa - Nhemachena, Charles; Hassan, Rashid M. (RePEc: Research Papers in Economics, 2007)
Adaptation to climate change involves changes in agricultural management practices in response to changes in climate conditions. It often involves a combination of various individual responses at the farm-level and assumes that farmers have access to alternative practices and technologies available in the region. This study examines farmer adaptation strategies to climate change in Southern Africa based on a cross-section database of three countries (South Africa, Zambia and Zimbabwe) collected as part of the Global Environment Facility/World Bank (GEF/WB) Climate Change and African Agriculture Project. The study describes farmer perceptions to changes in long-term temperature and precipitation as well as various farm-level adaptation measures and barriers to adaptation at the farm household level. A multivariate discrete choice model is used to identify the determinants of farm-level adaptation strategies. Results confirm that access to credit and extension and awareness of climate change are some of the important determinants of farm-level adaptation. An important policy message from these results is that enhanced access to credit, information (climatic and agronomic) as well as to markets (input and output) can significantly increase farm-level adaptation. Government policies should support research and development on appropriate technologies to help farmers adapt to changes in climatic conditions. Examples of such policy measures include crop development, improving climate information forecasting, and promoting appropriate farm-level adaptation measures such as use of irrigation technologies. from Authors' Abstract
Keywords: openalex:import

Micro-Level Analysis of Farmers’ Adaptation to Climate Change in Southern Africa - Nhemachena, Charles; Hassan, Rashid M. (RePEc: Research Papers in Economics, 2007)
Adaptation to climate change involves changes in agricultural management practices in response to changes in climate conditions. It often involves a combination of various individual responses at the farm-level and assumes that farmers have access to alternative practices and technologies available in the region. This study examines farmer adaptation strategies to climate change in Southern Africa based on a cross-section database of three countries (South Africa, Zambia and Zimbabwe) collected as part of the Global Environment Facility/World Bank (GEF/WB) Climate Change and African Agriculture Project. The study describes farmer perceptions to changes in long-term temperature and precipitation as well as various farm-level adaptation measures and barriers to adaptation at the farm household level. A multivariate discrete choice model is used to identify the determinants of farm-level adaptation strategies. Results confirm that access to credit and extension and awareness of climate change are some of the important determinants of farm-level adaptation. An important policy message from these results is that enhanced access to credit, information (climatic and agronomic) as well as to markets (input and output) can significantly increase farm-level adaptation. Government policies should support research and development on appropriate technologies to help farmers adapt to changes in climatic conditions. Examples of such policy measures include crop development, improving climate information forecasting, and promoting appropriate farm-level adaptation measures such as use of irrigation technologies. from Authors' Abstract
Keywords: openalex:import; openalex:yes

Micro-Level Analysis of Farmers’ Adaptation to Climate Change in Southern Africa - Nhemachena, Charles; Hassan, Rashid M. (RePEc: Research Papers in Economics, 2007)
Adaptation to climate change involves changes in agricultural management practices in response to changes in climate conditions. It often involves a combination of various individual responses at the farm-level and assumes that farmers have access to alternative practices and technologies available in the region. This study examines farmer adaptation strategies to climate change in Southern Africa based on a cross-section database of three countries (South Africa, Zambia and Zimbabwe) collected as part of the Global Environment Facility/World Bank (GEF/WB) Climate Change and African Agriculture Project. The study describes farmer perceptions to changes in long-term temperature and precipitation as well as various farm-level adaptation measures and barriers to adaptation at the farm household level. A multivariate discrete choice model is used to identify the determinants of farm-level adaptation strategies. Results confirm that access to credit and extension and awareness of climate change are some of the important determinants of farm-level adaptation. An important policy message from these results is that enhanced access to credit, information (climatic and agronomic) as well as to markets (input and output) can significantly increase farm-level adaptation. Government policies should support research and development on appropriate technologies to help farmers adapt to changes in climatic conditions. Examples of such policy measures include crop development, improving climate information forecasting, and promoting appropriate farm-level adaptation measures such as use of irrigation technologies. from Authors' Abstract
Keywords: openalex:import